KINERJA VITAMIN C DAN TEMULAWAK TERHADAP KELANGSUNGAN HIDUP POST LARVA IKAN PAPUYU (Anabas testudineus Bloch) - Mustaqiim Pengestu; Untung Bijaksana; Indira Fitriliyani (Fish Scientiae, 2019)
Hatchery technology has been controlled but the technology is not maximized seed maintenance. Continuity seed in cultivation is indispensable. Vitamin C has a very big role in the physiology of fish primarily as an antioxidant and anti-stress and curcuma component containing a nutritious oil asitri. Curcumin stimulate liver cells to improveand facilitate the production and secretion of bile, there by improving digestion and accelerate gastric emptying.This study was conducted over five months starting from the preparation,execution, and reporting. This research was conducted in the village Mentaos, Banjarbaru, South Kalimantan. The parameters studied were weight growth, length growth, survival rate, feed conversion, protein retention and fat retention by using statistical test completely randomized design (CRD) with 4 treatments and 3 replications.A treatment using commercial feed shrimp with the codes FL 0, treatment and use of commercial feed, thoroughly mixed with vitamin C brand Sido Muncul C1000 much as1000 mg / kg feed, treatment C using commercial feed FL 0 thoroughly mixed withginger 150 g / kg of feed, and D treatment using commercial feed FL 0 thoroughly mixedwith vitamin C as much as 1000 mg / kg feed and ginger 150 g / kg of feed.The results showed that the commercial feed was given vitamin C and curcuma provide survival rate value and the best feed conversion in post larval climbing perch. Best survival value 23.49% and feed conversion value of 0.51. The results of research into the use of vitamin C and curcuma can be recommended to farmers fish farmers to increase the value of the survival of post larvae climbing perch.